+0  
 
0
279
1
avatar

rearrange y=p-2qx^2    

to make x the subject of the formula

Guest Apr 10, 2016
Sort: 

1+0 Answers

 #1
avatar+11348 
0

y=p-2qx^2 

y-p = -2qx^2

-(y-p) / 2q = x^2

 

x= sqrt(( p-y)/2q)

ElectricPavlov  Apr 10, 2016

24 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details